Assam as India gateway to ASEAN.
The geostrategic location of Assam offers opportunities for enhancing regional and cross border trade and developing economic corridors between India and regional neighbors in Southeast Asia. This builds on the vision for Assam to follow an outward looking growth strategy and become a 75 billion economy by 2025. The vision is also geared toward ensuring that both the state and the country remain committed toward achieving the Sustainable Development Goals.